(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
Methotrexate competitively inhibits dihydrofolic acid reductase and thereby inhibits DNA synthesis and cellular replication.This study describes a simple and fast high-performance liquid chromatography method for the determination of methotrexate [MTX] in serum.samples were collected from adult cancer patients receiving high dose MTX at Mahathma Gandhi Memorial hospital (Warangal,AP.India) at various time intervals after the end of each infusion. Serum was deproteinized with trichloroacetic acid and the supernatant was injected into a 250×4.6 mm octadecylsilane column. Mobile phase was made of TRIS-phosphate buffer (pH 5.7): methanol: acetonitrile (70:20:10) with a flow rate of 1ml/min. Ultraviolet detection was done at 313 nm and at ambient temperature. Para aminoacetophenone was used as internal standard. Methotrexate and internal standard retention times were 4.6 and 9.5 minutes, respectively. Results showed that reproducibility (precision) of method within a day was 2.6 to 6 percent and between days was 5.5 to 9.5 percent. The recovery of the method was between 61.5 and 72.7 percent. The quantitation limit of the method for methotrexate was 0.1μM. This method is suitable for quantitation of methotrexate after infusion of high doses of this drug and has good accuracy, precision and quantitation limit. Key Words: Methotrexate; HPLC; Serum Concentration. DOI: 10.3329/sjps.v2i1.1693 Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 8-13